2015
DOI: 10.1093/chromsci/bmv189
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of an HPLC–UV Procedure to Determine Multiple Flavonoids and Phenolics inAcanthopanaxLeaf Extracts

Abstract: Acanthopanax species are used in traditional medicine to treat numerous diseases. A simultaneous high-performance liquid chromatography (HPLC) method was developed and validated for the determination of the flavonoid and phenolic content of Acanthopanax leaves. HPLC analysis was performed on an AKZO NOBEL Kromasil 100-5C 18 column (250 × 4.6 mm, 5 µm) using a gradient elution of acetonitrile-water containing 0.2% formic acid with a flow rate of 1.0 mL/min, monitored at 320 nm. The method was linear over the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…23 Many studies have revealed that rutin is good for human health, such as antibacterial, antiulcer, anti-inflammatory, antiarrhythmia, antitumor, protective and expanding blood vessel. 24,25 Up to now, lots of analytical methods have been applied for the determination of rutin, including chemiluminescence, 26,27 high-performance liquid chromatography (HPLC), 28,29 capillary electrophoresis spectrophotometry, 30,31 UV-Vis spectrophotometry 32 and electrochemical methods. [33][34][35][36] In this work, Cu-doped carbon quantum dots (Cu-CQDs) were prepared by a facile one-step pyrolytic synthesis using Na 2 [Cu(EDTA)] as precursor.…”
Section: Introductionmentioning
confidence: 99%
“…23 Many studies have revealed that rutin is good for human health, such as antibacterial, antiulcer, anti-inflammatory, antiarrhythmia, antitumor, protective and expanding blood vessel. 24,25 Up to now, lots of analytical methods have been applied for the determination of rutin, including chemiluminescence, 26,27 high-performance liquid chromatography (HPLC), 28,29 capillary electrophoresis spectrophotometry, 30,31 UV-Vis spectrophotometry 32 and electrochemical methods. [33][34][35][36] In this work, Cu-doped carbon quantum dots (Cu-CQDs) were prepared by a facile one-step pyrolytic synthesis using Na 2 [Cu(EDTA)] as precursor.…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies have revealed that Acanthopanax spp. are rich in saponins , flavonoids , phenolics , terpenes , lignans , and other compounds . Various species including Acanthopanax senticosus, Acanthopanax gracilistylus , and Acanthopanax koreanum are particularly rich in saponins, which are considered to be the chemical markers of Acanthopanax .…”
Section: Introductionmentioning
confidence: 99%
“…19) Among Acanthopanax species, the leaves of Acanthopanax senticosus inhibit adipogenesis through down-regulation of lipoprotein lipase in 3T3-L1 cells. 21,22) Moreover, 50% ethanol extract is useful in treating non-alcoholic fatty liver disease in ob/ob mice and it reduces body weight gain in high-fat diet-induced obese mice. 23) This study focused on exploring the possibility that some plants belonging to the same Acanthopanax species might have effects on obesity or related disorders.…”
Section: Discussionmentioning
confidence: 99%